Europeanisation of Crime Prevention (Archives of Criminology, 2019)
The text offers an analysis of the development of joint activities for crime prevention in Europe since the unification movement. The author mentions that one of the common goods for which the European community decided to fight beyond national borders was international security. The importance of security was first emphasised in the European Treaty of Maastricht under the ‘third pillar’. Preventive police cooperation was intended to prevent primarily terrorist attacks, illegal drug trafficking, and other significant forms of international crime. Janina Czapska notes that a common endeavour to maintain security was evidenced by a gradual tightening and formalisation of cooperation between states, resulting in the establishment of new European institutions of the justice system. Consequently, the article describes the successive stages of shaping the prevention policy in the European Union. A particular emphasis is placed on discussing the Communication of the Council and the European Parliament on crime prevention in the Union from March 2004. The Communication played an important role in the Europeanisation of crime prevention, as it presented its legal basis, the concepts of common crime, and an analysis of new trends in crime development. The article also mentions institutional forms of joint activities in the area of prevention, such as the establishment of the European Crime Prevention Network, of which Poland has been a member since 2004. Examples and forms of its activities are widely discussed by Czapska in this study, who concludes by stating that in a general assessment of the degree of Europeanisation of crime prevention in the Polish framework, the role played by the partnership with the Netherlands and the United Kingdom in the 1990s should not be forgotten.